Esculpiendo la forma negra. La conceptualización de las artes visuales afrodescendientes en la obra de Teodoro Ramos Blanco. - García Yero, Cary Aileen (Anuario de Historia de América Latina, 2025)
Within Latin American visual arts, the name Teodoro Ramos Blanco remains largely unknown, despite being one of the most significant sculptors of Cuba’s Republican period. This is unsurprising given the systematic exclusion of Afrodescendant artists from the hemisphere’s art histories. Ramos Blanco created the sculptures for iconic public works in Cuba and Haiti, he exhibited throughout the region, and trained generations of artists and advanced the nation’s cultural life through his work with the Círculo de Bellas Artes (CBA) and the National Academy of Fine Arts San Alejandro. This article highlights an unexplored dimension, not only of his pioneering work but also of the region’s art histories. It traces the origins of conceptualizations of Afrodescendant visual arts envisioned by Afro-Latin American artists. Beyond his pioneering output and his pedagogical and administrative contributions, Ramos Blanco stands out for his exceptional writings on race and the arts, where he conceptualized what he called the black form in the 1930s. His framework was explicitly diasporic and antiracist, sculpting the Afrodescendant character as a resilient and transformative force. This article weaves together his biography, his work, and his conception of the black form, broadening the coordinates of thought and action of Afro-Latin American artists while illuminating the legacy of this sculptor.